Family Intervention In The Treatment Of Female Juvenile Delinquency: A Qualitative Study In The Collectivist Society - Melati Sumari; Fatahyah Yahya; Mohd Radhi Abu Shahim; Dini Farhana Baharudin (Sage Publication, 2024)
Indexed by Scopus/ERA